Magnetic phase diagram, magnetoelastic coupling, and Grüneisen scaling in CoTiO3 - Hoffmann, Marco; Dey, Kaustav; Werner, Johannes; Bag, R.; Kaiser, Jakob; Wadepohl, Hubert; Skourski, Y.; Abdel-Hafiez, M.; Singh, S.; Klingeler, Rüdiger (Physical review, 2021)
High-quality single crystals of CoTiO3 are grown and used to elucidate in detail structural and magnetostructural effects by means of high-resolution capacitance dilatometry studies in fields up to 15 T which are complemented by specific heat and magnetization measurements. In addition, we refine the single-crystal structure of the ilmenite (R¯3) phase. At the antiferromagnetic ordering temperature TN pronounced λ-shaped anomaly in the thermal expansion coefficients signals shrinking of both the c and b axes, indicating strong magnetoelastic coupling with uniaxial pressure along c yielding six times larger effect on TN than pressure applied in-plane. The hydrostatic pressure dependency derived by means of Grüneisen analysis amounts to ∂TN/∂p≈2.7(4)K/GPa. The high-field magnetization studies in static and pulsed magnetic fields up to 60 T along with high-field thermal expansion measurements facilitate in constructing the complete anisotropic magnetic phase diagram of CoTiO3. While the results confirm the presence of significant magnetodielectric coupling, our data show that magnetism drives the observed structural, dielectric, and magnetic changes both in the short-range ordered regime well above TN as well as in the long-range magnetically ordered phase.